Is Social Interaction Related to the Event of Nomophobia in High School Students in Semarang? - Ahya Sari Dian Nitami; Betie Febriana; Dwi Heppy Rochmawati (Universitas Muhammadiyah Semarang, 2020)
Teens in one day of care often lose smartphones more than 34 times a day and feel fear and anxiety when their smartphones, smartphones have a negative impact on adolescents which can result in decreased social skills. The purpose of this study was to see the relationship between interaction interactions with the incidence of nomophobia among high school students in Semarang. This research uses quantitative methods. The researcher used simple random sampling technique with questionnaire to 178 students as the respondents. The results obtained from statistical tests using the Chi-Square formula. Based on the results of the analysis obtained that from 178 research respondents, 128 respondents aged 16 years (71.9%) and 108 women (60.7%), Most social people were in the high category 102 people (57.3%) and the most nomophobia was in the moderate nomophobia category 133 people (74.7%). There is no relationship between social interaction and the incidence of nomophobia among SMA N 10 Semarang students (p value> 0.05).